Wave patterns organize cellular protrusions and control cortical dynamics. Issue 3 (12th March 2019) - Miao, Yuchuan; Bhattacharya, Sayak; Banerjee, Tatsat; Abubaker‐Sharif, Bedri; Long, Yu; Inoue, Takanari; Iglesias, Pablo A; Devreotes, Peter N
Abstract: Cellular protrusions are typically considered as distinct structures associated with specific regulators. However, we found that these regulators coordinately localize as propagating cortical waves, suggesting a common underlying mechanism. These molecular events fell into two excitable networks, the signal transduction network STEN and the cytoskeletal network CEN with different wave substructures. Computational studies using a coupled‐network model reproduced these features and showed that the morphology and kinetics of the waves depended on strengths of feedback loops. Chemically induced dimerization at multiple nodes produced distinct, coordinated alterations in patterns of other network components. Taken together, these studies indicate: STEN positive feedback is mediated by mutual inhibition between Ras/Rap and PIP2, while negative feedback depends on delayed PKB activation; PKBs link STEN to CEN; CEN includes positive feedback between Rac and F‐actin, and exerts fast positive and slow negative feedbacks to STEN. The alterations produced protrusions resembling filopodia, ruffles, pseudopodia, or lamellipodia, suggesting that these structures arise from a common regulatory mechanism and that the overall state of the STEN‐CEN system determines cellular morphology. Synopsis: Theoretical and experimental analyses indicate that signal transduction (STEN) and cytoskeletal (CEN) excitable networks interact to control dynamic wave patterns at the cell cortex. Network perturbations change wave speed and range and create distinct protrusions. Cell cortical wave patterns are brought about by coupled Rap/Ras and Rac/F‐actin centric networks that are linked via PIP3/PKBs. Increases in Rap/Ras or decreases in PIP2 activate while PIP3/PKBs negatively regulate STEN. Increasing Rac/F‐actin activates CEN and provides feedback to STEN. Feedback strengths of the coupled excitable networks control speed and range of wave patterns. Protrusive form and dynamic cell morphology are determined by the overall state of the coupled networks rather than single regulators. Abstract : Theoretical and experimental analyses indicate that signal transduction (STEN) and cytoskeletal (CEN) excitable networks interact to control dynamic wave patterns at the cell cortex. Network perturbations change wave speed and range and create distinct protrusions.